PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA - Copo, Sri Dewi; Otaya, Lian Gafar; Huljannah, Mifta (DIRASATUL IBTIDAIYAH, 2024)
The problems that will be discussed in this thesis are (1). How to apply the Problem Based Learning model to improve the ability to solve story problems on ordinary fractions for class IV students at SDN 9 Limboto. The research model is classroom action research by Kemmis Mc Taggart. The research subjects were 11 class IV students at SDN 09 Limboto. Data collection techniques are carried out by means of test questions, observation, interviews and documentation. The research stages have four models, namely: preparation (planning), action implementation, monitoring and evaluation (observation), analysis and reflection. The results of the research show that Problem Based Learning activities to improve students' abilities in solving story problems in class IV at SDN 09 Limboto can be seen from the percentages obtained. During the pre-cycle the average percentage was 9% before action was taken, then after action was taken in cycle I the average percentage value increased to 54% and increased again in cycle II with an average percentage value of 90% and had reached the success rate is 75%. Therefore, the Problem Based Learning model can improve students' abilities in solving questions and problems on ordinary fractions in class IV SDN 09 Limboto.Keywords: Problem Based Learning Model; Ordinary Fractions; Mathematics.Permasalahan yang akan dibahas dalam skripsi ini yakni (1). Bagaimana penerapan model Problem Based Learning untuk dapat meningkatkan kemampuan menyelesaikan soal cerita materi pecahan biasa pada peserta didik kelas IV SDN 9 Limboto. Model penelitian adalah penelitian tindakan kelas oleh KemmisMc Taggart. Subjek penelitian yakni peserta didik kelas IV SDN 09 Limboto yang berjumlah 11 orang. Teknik pengumpulan data dilakukan dengan cara tes soal, observasi, wawancara dan dokumentasi. Tahapan penelitian memiliki empat model yaitu: persiapan (perncanaan),pelaksanaan tindakan, pemantauan dan evaluasi (pengamatan), analisis dan refleksi. Hasil penelitian menunjukan kegiatan Problem Based Learning untuk meningkatkan kemampuan peserta didik dalam menyelesaikan soal cerita di kelas IV SDN 09 Limboto dapat dilihat dari jumlah-jumlah prsentase yang didapatkan. Pada saat pra-siklus presentase rata-rata yakni 9% sebelum dilakukan tindakan, kemudian setelah dilakukan tindakan pada siklus I nilai presentase rata-rata meningkat yakni 54% dan meningkat lagi pada siklus II dengan nilai presentase rata-rata yakni 90% dan sudah mencapai tingkat keberhasilan yakni 75%. Maka dengan itu model Problem Based Learning dapat meningkatkan kemampuan peserta didik dalam menyelesaikan soal certa materi pecahan biasa di kelas IV SDN 09 Limboto.Kata Kunci: Model Problem Based Learning; Pecahan Biasa; Matematika.